BELENGGU ATURAN, NEGOSIASI, DAN EKSISTENSI RADIO KOMUNITAS: Studi pada Radio Balai Budaya Minomartani dan Wijaya di Yogyakarta - Eddyono, Aryo Subarkah; Hanathasia, Mirana (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2018)
Licensing issues are one thing that puts a burden on community radios, radios that are established to serve the information and entertainment needs of a particular community and are not justified in seeking benefits like private radio. Another thing is about the rules of advertising where community radio is not allowed to broadcast commercial advertisements, as well as canalization rules problems or broadcast frequency restrictions. This research answers the negotiations conducted by the Balai Minomartani (BBM) radio station and Radio Wijaya in Yogyakarta in obeying the government's burdensome rules and what their motivations. Data obtained from in-depth interviews, online and offline observations, and document collection. The results showed that the negotiations carried out by such two radio related to the troublesome and burdensome rules were to obtain legality and carry out the mandate of the community because legality became an important capital for the existence of community radio and to obtain various accesses. To cite this article (7th APA style): Eddyono, A. S. & Hanathasia, M. (2018). Belenggu Aturan, Negosiasi, dan Eksistensi Radio Komunitas [The Shackle of Regulation, Negotiation, and Existence of the Community Radio]. Journal Communication Spectrum, 8(1), 15-44. http://dx.doi.org/10.36782/ jcs.v8i1.1810